(untitled) (Iter, 2022)
Dante’s presence in Chile is widely evident and it is backed up by documented and concrete facts andpeople from our academic environment. However, “The outcast ” drama from Vittorio di Girolamo, winner of “Experimental Drama ” prize from P.U.C.Ch. in 1999, goes further beyond. It brings the character Dante Alighieri straight on stagey re-interpreting it freely, to the light of a faithfulness to the spirit which transcends faithfulness to historical reality of time. The daily, poetic, and mystical worid, interweave in these “ Dantesque experiences ” which the author of the drama narrates and illustrates with his astonished passion and mastery.